Hand Hygiene Compliance Behavior and Glove Use in the Pediatric Intensive Care Unit During COVID-19 Pandemic - Bangkit Putrawan; Dominicus Husada; Parwati Setiono Basuki; Risa Etika; Ismoedijanto; Dwiyanti Puspitasari; Leny Kartina (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The condition of Covid-19 pandemic potentially influences hand hygiene compliance as aresult of workload changes, increased awareness of healthcare workers (HCWs) and personal protectiveequipment procedures, especially in terms of hand glove use,Objective to know the adherence of healthcare workers at the pediatric intensive care unit (PICU) to complywith hand hygiene and glove use during the pandemic.Methods An observational prospective study was carried out including all HCWs stationed at the PICU DrSoetomo General Hospital during January 2021. All participants were to sign an informed consent beforethe study took place. A target of 500 opportunities was estimated during the observation, and recorded usinginfra-red cameras placed at ten points. Hand hygiene compliances were evaluated according to the videosurveillance records by an independent auditor. Compliance was measured by dividing total number ofobserved appropriate hand hygiene by the sum of opportunities. Data were analysed using Chi Square testat a significance of p<0.05.Results: A total of 28 HCWs were eligible for the study; 9 were excluded. The majority were female(21; 75%), the mean age was 37.9 (SD 5.2) years. During 72 hours’ observation among 526 glove-useopportunities 104 (19.7%) actual glove-use episodes were evident. The hand hygiene compliance was lower(41.3%) when wearing gloves as compared to those with no glove use (68.2%) (p<0.001).